Aerobic exercise training in children and adolescents with inflammatory bowel disease: Influence on psychological functioning, sleep and physical performance – An exploratory trial. (October 2017) - Mählmann, Laura; Gerber, Markus; Furlano, Raoul I.; Legeret, Corinne; Kalak, Nadeem; Holsboer-Trachsler, Edith; Brand, Serge
Abstract: People with Inflammatory Bowel Disease (IBD) are at risk for mental health issues, poor sleep quality and limited engagement in physical activity (PA). Standard treatment consists of immune modulating pharmaceuticals though evidence is growing that aerobic exercise training (AET) could serve as an adjuvant option to reduce disease symptoms and improve mental health. The aim of the present exploratory trial was to investigate possible AET effects on psychological functioning, symptoms of depression, sleep and physical activity in paediatric patients with IBD. Twenty-one paediatric patients with IBD and 23 gender- and age-matched healthy controls (HC) were assessed. The IBD group was further split into a "remission-group" (IBD-RE; n = 14) and an "active disease group" (IBD-AD; n = 7). All participants completed an 8-week AET exergame intervention reaching 60–80% of maximum heart rate for 5 days per week. At baseline and after 8 weeks, psychological functioning, depressive symptoms, objective sleep EEG, subjective sleep and objective and subjective PA were assessed. AET improved the exercise capacity of all participants. Self-reported fitness and daily physical activity increased in IBD-AD, but not in IBD-RE and HC. No improvements were observed for psychological functioning, depressive symptoms or subjective sleep. Objective sleep improved, deep sleep increased, light sleep decreased, and in the IBD-AD group the number of arousals after sleep onset decreased. Descriptively, the IBD-AD group reported lower psychological functioning and poorer subjective sleep quality. Among paediatric patients with IBD and healthy controls, an exergaming intervention has the potential to improve exercise capacity, self-reported fitness, daily physical activity, and aspects of objective sleep. Results suggest that children and adolescents in an active state of IBD are at increased risk of poor psychological functioning and poor sleep quality. Highlights: We performed an aerobic exercise training (AET) in paediatric patients with IBD and healthy controls. AET increased exercise capacity, self-reported fitness and daily PA. AET had no influence on psychological functioning and subjective sleep. AET is suitable also for paediatric patients with IBD. AET improved specific domains of objective sleep.